Thinking outside the 'box': a discussion of sports fans, teams, and the environment in the context of COVID-19 - Mastromartino, Brandon; Ross, Walker J.; Wear, Henry; Naraine, Michael L. (Sport in society, 2020)
In this paper, we examine the implications of sport stadiums closures during the COVID-19 global pandemic. The paper looks at the impact of sport stadium closures from three perspectives: The individual fan, the sport organization, and societal implications, with specific consideration to the environment. Previous literature was reviewed in order to highlight the areas in which the sport industry will need to focus their attention to in the coming months and provide theoretical background for academics looking to identify unique research opportunities. With an understanding of the implications of sport stadium closures to the sport world and beyond, academics and practitioners can work to solve the problems that lie ahead during and after the COVID-19 crisis.